Pertanggungjawaban Direksi BUMN Terhadap Kerugian Negara Berdasarkan Regulasi Pemerintahan Sektor Perusahaan Dan Pidana - Afrilia, Dian; Sayit Bandung Bondowoso (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
This paper provides an in-depth analysis of the accountability of directors of State-Owned Enterprises (SOEs) for state financial losses from the perspectives of corporate law and criminal law. The core issue lies in the tension between two legal regimes with contrasting orientations: corporate law, which emphasizes professionalism, managerial discretion, and protection against business risks through the business judgment rule doctrine; and criminal law, particularly the Anti-Corruption Law, which focuses on the consequences of actions in the form of financial losses to the state. In practice, this divergence often leads to legal uncertainty and overlaps, as business losses are frequently equated with unlawful acts subject to criminal sanctions. This paper argues that a repressive approach one that disregards rational decision-making processes has created fear among directors, resulting in a chilling effect that negatively impacts the management of SOEs. Therefore, a normative and institutional integration is urgently needed, placing the business judgment rule, the principle of lex posterior derogat legi priori, and the ultima ratio principle as foundational elements in assessing directors’ liability. The main conclusion of this study emphasizes the necessity of harmonizing corporate and criminal law to ensure legal certainty, maintain the continuity of SOE operations, and uphold the integrity of the national legal system.